تطوير وسائط تعليم اللغة العربية على أساس جوجل سايت لتحسين تعلم املفردات لطالبالصف السادسبمدرسةالشاذلي االبتدائية اإلسالمية - Soleh, Moh; Al-Anshori, Toriq (Lugawiyyat, 2024)
This research was motivated by observation data which showed the low learning outcomes of female students in grade VI Arabic language material. Researchers conducted research using a Research and Development approach to improve student learning outcomes. The objectives of this research are: (1) increase students' knowledge about the application of Google Sites learning to improve learning outcomes, and (2) increase students' knowledge about the use of Google Sites learning to improve learning outcomes. This research uses the ADDIE development model and was conducted at MI Tahfidz Asy Syadzili 4 Gondanglegi Malang. This research measures all areas of learning outcomes, namely cognitive, affective and psychomotor. Each research cycle shows improvements in all areas. Google Sites learning allows students to gain handson learning experience and improve student learning outcomes. Based on this data, it is recommended that teachers use Google Sites learning in Arabic language learning in class VI Mi Tahfidz Asy Syadzili 4 Gondanglegi Malang to improve student learning outcomes. Keywords: google sites, teaching media, vocabulary,